STRENGTHENING INSTITUTIONS IN THE EFFORT ADAT CUSTOMARY LAW ENFORCEMENT IN ILLEGAL GOLD MINING AREAS AFFECTED - sujianto; ikhsan; syofian; MY Tiyas Tinov (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2019)
Revitalization of customary and legal institutions is very urgent for the sustainability of environmental. Environmental damage due to illegal gold mining has been very alarming which will have an impact on health problems and natural disasters (flooding). This happens regardless of economic problems mainly due to the stagnation of the prices of superior commodities in Kuantan Singingi Regency. other than that based on the results of observations of these researchers also caused by the weakening of customary institutions. The purpose of this study focuses on the customary institutions that exist in this area because in this sub-district they have traditional institutions in the form of people. This research method uses a qualitative approach with data collection techniques with interviews, observation and documentation. Data analysis technique with interactive analysis. The results of the study indicate that there is a weakening of institutional functions of customary law in preventing environmental damage. Whereas in the previous traditional institutions regulating the ways to manage the environment. Other findings of the local government reduced the role of adat in regulating their communities, whereas in some villages it was proven to be able to protect the environment by prioritizing the functions of traditional institutions.